Q&A - Ask Doubts and Get Answers
Q

Show that (4pq+3q)^2 - (4pq-3q)^2 = 48pq^2

Q : 5      Show that.

             (iv)  (4pq+3q)^2-(4pq-3q)^2=48pq^2

Answers (1)
Views

Opening both brackets we get,

                    (4pq+3q)^2-(4pq-3q)^2 = 16p^2q^2 + 24pq^2 + 9q^2 - (16p^2q^2 - 24pq^2 + 9q^2)

                                                                          = 16p^2q^2 + 24pq^2 + 9q^2 - 16p^2q^2 + 24pq^2 - 9q^2)

                                                                          = 48pq^2

                                                                           = R.H.S.

Exams
Articles
Questions